Pengaruh Penggunaan Media Audio Visual terhadap Hasil Belajar Siswa pada Materi Sistem Ekskresi - Wilda Rizkiyahnur Nasution (Institut Agama Islam Negeri, 2022)
This study aims to determine whether there is an effect of using audio-visual media on student learning outcomes in the excretory system material. The population in this study were students of class XI IPA MAN 1 Padangsidimpuan as many as 4 classes and samples obtained randomly as many as 2 classes, namely class XI IPA1 as an experimental class using audio-visual media and class XI IPA3 as a control class without using audio-visual media. . The instrument in this study used a multiple-choice learning outcome test. The data analysis technique used a one-part t-test. The results of the post-test data hypothesis test obtained tcount = 7.46 and ttable = 1.671 at the significance level = 0.05 so that tcount ttable means Ha is accepted and Ho is rejected. Thus it can be concluded that student learning outcomes using audiovisual media are higher than those without using audiovisual media in the excretory system material.